Comparative study of three expeller process soybean meals in diets for lactating dairy cows - Burgos, V.; Titgemeyer, Evan C.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty-eight primiparous Holstein cows were used in two simultaneous 3×3 Latin squares with 28-day periods to evaluate expeller soybean meal from three sources. Six pens containing eight cows each were utilized. Cows were pen fed diets formulated in accordance with NRC (2001) recommendations and based on the assumption that the three sources of soybean meal were nutritionally identical. Diets contained on a dry matter basis, 24.3% chopped alfalfa hay, 9.3% field processed corn silage, 9.2% whole fuzzy cottonseed, 19.2% wet corn gluten feed (Minnesota Corn Processors, Inc., Columbus, NE), and 38% grain mix (70.2% dry rolled corn grain, 18.44% expeller soybean meal, 2.15% wet molasses, 3.47% Menhaden fish meal, and 5.74% min/vit premix). The sources of expeller soybean meal were Grain States Soya, Inc., West Point, NE; NCKP, LLC., Washington, KS; and Bruning Grain and Feed, Bruning, NE. All cows averaged 77 lbs. of milk and consumed approximately 55 lbs. of dry matter daily. Dry matter intake averaged 3.9% of body weight and their production efficiency (ECM/DMI) was 1.45. No differences due
Keywords: Dairy; Soybean; Expeller processed; Cows